Analisis Strategi Pengembangan Usaha Butik - Sutrisno Sutrisno (Neolectura, 2022)
This research is a qualitative descriptive research, with a case study approach. The population and samples in this study are boutique owners, employees, customers by means of interviews and documentation focused on Strengths, Weaknesses, Opportunities and Threats to make a SWOT analysis as the basis for the Boutique's business development strategy. Based on the results of the IFAS matrix with a score of 3.05 and the EFAS matrix of 2.93, it is known that the position of the boutique in the IE matrix is in quadrant IV, namely growth and build. The most appropriate strategy used by this boutique is an intensive strategy (market penetration and product development). Alternative strategies generated in the SWOT matrix are obtained by applying intensive strategies. There are 10 alternative strategies that can be applied by Salimah Boutique based on SWOT matrix analysis, namely: maintaining quality and elegant products according to Islamic law (SO1), maintaining customer or reseller loyalty (SO2), utilizing technology to improve marketing (SO3), increasing online promotion (WO1), recruiting new employees to manage products sold online (WO2), improving product quality and making different products (ST1), maintaining the tastes that customers want (ST2), increasing promotion through integrated social media in all marketplaces (WT1), improving the quality of employees (WT2), seeking additional capital or investors (WT3).